Cholesterol-conjugated stapled peptides inhibit Ebola and Marburg viruses in vitro and in vivo - Pessi, Antonello; Bixler, Sandra L.; Soloveva, Veronica; Radoshitzky, Sheli; Retterer, Cary; Kenny, Tara; Zamani, Rouzbeh; Gomba, Glenn; Gharabeih, Dima; Wells, Jay; Wetzel, Kelly S.; Warren, Travis K.; et al. (Antiviral research, 2019)
Filoviridae currently includes five official and one proposed genera. Genus Ebolavirus includes five established and one proposed ebolavirus species for Bombali virus (BOMV), Bundibugyo virus (BDBV), Ebola virus (EBOV), Reston virus (RESTV), Sudan virus (SUDV) and Taï Forest virus (TAFV), and genus Marburgvirus includes a single species for Marburg virus (MARV) and Ravn virus (RAVV). Ebola virus (EBOV) has emerged as a significant public health concern since the 2013–2016 Ebola Virus Disease outbreak in Western Africa. Currently, there are no therapeutics approved and the need for Ebola-specific therapeutics remains a gap. In search for anti-Ebola therapies we tested the idea of using inhibitory properties of peptides corresponding to the C-terminal heptad-repeat (HR2) domains of class I fusion proteins against EBOV infection. The fusion protein GP2 of EBOV belongs to class I, suggesting that a similar strategy to HIV may be applied to inhibit EBOV infection. The serum half-life of peptides was expanded by cholesterol conjugation to allow daily dosing. The peptides were further constrained to stabilize a helical structure to increase the potency of inhibition. The EC50s of lead peptides were in low micromolar range, as determined by a high-content imaging test of EBOV-infected cells. Lead peptides were tested in an EBOV lethal mouse model and efficacy of the peptides were determined following twice-daily administration of peptides for 9 days. The most potent peptide was able to protect mice from lethal challenge of mouse-adapted Ebola virus. These data show that engineered peptides coupled with cholesterol can inhibit viral production, protect mice against lethal EBOV infection, and may be used to build novel therapeutics against EBOV. •The 23 amino acid Ebola GP2 C-terminal Heptad-repeat domain was designed as an Ebola fusion inhibitor.•The peptide inhibitor has been “stapled” and conjugated with PEG/cholesterol to improve potency and systemic exposure.•Potency (EC50) versus authentic Ebola virus was in the single digit micromolar range in both human and rodent cell lines.•The best peptide provided survival advantage in mice against lethal Ebola challenge and suggested utility of the approach.